Estudo da liberação in vitro da progesterona a partir de cáspsulas de gelatina mole: desenvolvimento e validação de método de dissolução - BERRETTA, Mariana de Oliveira (2010)
Progesterone is a steroid hormone used to treat uterin disfunction, such as hemorrhage and secondary amenorrhea, contraception, hormone replacement therapy in postmenopausal women, as well as in luteal phase support cases in assisted reproduction techniques. However, it presents low oral bioavailability because of its weak water solubility and intense hepatic metabolism. So, progesterone administration is carried out, mainly, through micronized drug dispersed in oils and surfactant formulations, in soft gelatin capsules, trying to improve oral bioavailability. However, there are no official compendia notifications about dissolution methods used to evaluate progesterone release from these dosage forms. Thus, this study proposes progesterone containing soft gelatin capsules dissolution method development and validation aiming to analyze two pharmaceutical specialties (called A and B) in vitro dissolution profile commercially available. Many conditions were evaluated in the study, such as dissolution medium different compositions (pH and surfactant variations), speed of agitation and apparatus (basket, paddle). In this study, reference product A was used as model and ANOVA/Tukey tests were carried out for statistic analysis, with 95% confidence interval. Dissolution method was validated according to selectivity, linearity, accuracy (recovery) and precision parameters. Both products were compared through dissolution profile, release kinetics and dissolution efficiency. Samples quantification was accomplished through high performance liquid chromatography (HPLC), validated through selectivity, linearity, precision, accuracy, detection and quantification limits parameters. Analyzing used conditions, statistic tests, and considering biorelevant characteristics, it was found that dissolution method more appropriate was the one that used paddle, sodium acetate buffer pH 4.5 with 3,0% of sodium lauryl sulfate dissolution medium, volume of 1000 mL, speed of agitation of 150 rpm and temperature of 37° C ± 0,5° C. This method showed to be specific, linear, precise and accurate. After products analysis, it was possible to notice that product B presented the best in vitro performance in the first four hours of test, best dissolution efficiency and that both showed first order kinetics. Quantification method by HPLC was appropriate for analysis, because it showed to be selective, linear, precise and accurate, with detection limit of 44,6 μg/mL and quantification limit of 148,6 μg/mL. Therefore, it is possible to conclude that dissolution method developed and validated showed to be appropriate for analysis, allowing to visualize differences between same batch units and among different pharmaceutical specialties.